Applying the Semantics of Spatial Prepositions and Error Correction to Teach the Spatial Prepositions “In” and “On - ATHMANI, Assma (Journal of Human Sciences, 2016)
Most teachers of English as a foreign language agree that a great number of learners use spatial prepositions inadequately and, despite the different techniques used in teaching them, most learners still consider learning the use of these prepositions one of the most problematic issues. The reason could be the various and close meanings and uses of each spatial preposition. Throughout this article, we will introduce the notion of the semantics of spatial prepositions (an organised and structured presentation of prepositions suggested by Cognitive Grammar), its importance and the semantics of both spatial prepositions in and on, in addition to an overview of the different types of error correction that can be used in the Grammar class. The results presented in this paper will show whether using error correction, presenting the semantics of spatial prepositions or using both techniques in combination would help teachers and students at the Department of English at the University of Constantine 1 in teaching and learning the spatial prepositions in and on.